Enhancing Healthcare Equity Through Cultural Competence Training: A Systematic Review of Impact and Implementation - Indi Dwi Shofi Yanti; Fatma Lutfiyatus Sayyida; Anggun Novia Indah Fitri (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
Cultural competence training has emerged as a critical strategy for improving healthcare delivery in increasingly diverse societies. This systematic review evaluates the impact of structured cultural competence interventions on key domains including doctor–patient communication, patient satisfaction, health equity, and cost-effectiveness. Drawing on evidence from peer-reviewed studies published between 2000 and 2024, the analysis identifies consistent improvements in clinical interactions, with enhanced cultural awareness, reduced implicit bias, and increased empathy among healthcare providers. Effective implementation strategies include experiential learning, digital platforms, mentorship, and integration into medical education and accreditation standards. Despite demonstrated benefits, challenges persist, such as inconsistent program design, limited evaluation frameworks, and insufficient institutional support for long-term integration. The findings underscore the need for standardized competency benchmarks, longitudinal training models, and policy alignment to ensure sustainability. When effectively implemented, cultural competence training contributes to equitable, patient-centered care by addressing systemic disparities and fostering trust in healthcare institutions. This review provides actionable insights for policymakers, educators, and healthcare leaders aiming to enhance service quality and inclusivity across multicultural settings.